1983
DOI: 10.1159/000233362
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Validation of Radioallergosorbent Tests for the Detection of Specific Human IgE Antibody Directed against Laboratory Animal Urinary Proteins

Abstract: Radioallergosorbent tests (RAST) using urinary proteins from mice, rats, guinea pigs and rabbits have been developed and used in the diagnosis of laboratory animal allergy (LAA). Of the 273 subjects tested, 15 had been previously diagnosed as laboratory animal allergic and 8 of these (53%) gave one or more positive RAST results. Of the 258 symptom-free individuals, only 9 (3.5%) had one or more positive RAST. Of these 9, 7 had previously worked with animals or had occupational exposure to the appropriate speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1984
1984
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Furthermore, high serum levels of specific IgG antibody to animal antigens, and of total IgE antibody, are potential sources oferror in the RAST. 22 There is evidence that smoking increases the risk of developing specific IgE antibody to occupational allergens and of developing symptoms of asthma. 23 There was a suggestion in these results of an association between LAA chest symptoms and current smoking and the role of smoking as a risk factor for Venables, Tee, Hawkins, Gordon, Wale, Farrer, Lam, Baxter, Newman-Taylor LAA is examined further in a companion paper.24 No previous study of LAA has suggested an association with smoking, but if present, there would clearly be potential for prevention and many firms already discourage smoking because of its established health risks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high serum levels of specific IgG antibody to animal antigens, and of total IgE antibody, are potential sources oferror in the RAST. 22 There is evidence that smoking increases the risk of developing specific IgE antibody to occupational allergens and of developing symptoms of asthma. 23 There was a suggestion in these results of an association between LAA chest symptoms and current smoking and the role of smoking as a risk factor for Venables, Tee, Hawkins, Gordon, Wale, Farrer, Lam, Baxter, Newman-Taylor LAA is examined further in a companion paper.24 No previous study of LAA has suggested an association with smoking, but if present, there would clearly be potential for prevention and many firms already discourage smoking because of its established health risks.…”
Section: Discussionmentioning
confidence: 99%
“…Skin prick tests with allergenic material may be performed, mainly by dermatologists and allergologists. More than 50070,however, will react positively to skin tests (Edwards et al, 1983b).…”
Section: Diagnosismentioning
confidence: 99%
“…The preva lence of allergic symptoms has been reported to be in the order of 19%, with 7.8% of the exposed popula tion experiencing asthma [7]. Some of these studies have reported the prevalence and distribution of IgG and IgE antibodies specific for urinary proteins in the individuals exposed to laboratory animals.Our own studies [8,9] have shown, using radioim munoassay, that 80% of symptomatic animal workers have specific IgG antibody to one or more of the com mon laboratory species, compared with 57% in asymptomatics and 6% in the unexposed population. Mean titres of specific IgG in symptomatic and asymptomatic groups were not significantly different.…”
mentioning
confidence: 93%
“…Rabbit anti-rat urinary protein served as the capture antibody on the microtitre plates (Immunolon M129-B, Dynatech) and fol lowing washing and blocking, crude urinary protein antigen was added. The human sera, diluted at 1/25, in a gelatin buffer containing 1 % normal rabbit serum to prevent any anti-rabbit IgG antibody present in the samples interfering with the assay [9,11], were then added to the washed plates. After washing, the mono clonal anti-IgG or subclass antibodies were incubated with the plates, and again, following washing, the al kaline phosphatase conjugated anti-mouse IgG anti body was added.…”
mentioning
confidence: 99%
See 1 more Smart Citation